HAKIKAT PERKEMBANGAN, PERBEDAAN DAN STRUKTUR BAHASA ANAK - M. Junaidi; Silvina Noviyanti; Dhiya Fathira Halim; Putri Ramadhani (STKIP Subang, 2025)
Children’s language development is a complex process shaped by biological maturation, cognitive readiness, and environmental experiences. At the primary school level, language ability serves as a foundation for literacy, social interaction, and academic success. This literature review examines the nature of children’s language development, individual differences in language acquisition, and the structural components of children’s language. The review synthesizes 20 empirical studies published between 2020 and 2025 focusing on developmental linguistics, first language acquisition, and early language education. Findings indicate that language development unfolds gradually through the acquisition of phonological, morphological, syntactic, semantic, and pragmatic skills. Individual variations arise from differences in linguistic input, interaction quality, socioeconomic conditions, cognitive development, and biological factors. Although primary school children exhibit increasingly systematic linguistic structures, phonological simplifications, morphological overgeneralizations, and pragmatic limitations remain common. The review highlights the importance of rich linguistic stimulation, meaningful social interaction, and responsive pedagogical approaches tailored to children’s developmental needs. Future research is encouraged to explore the use of digital media and multimodal approaches to support language growth in young learners.